Blood Pressure Variability as a Predictor of Left Atrial Dilatation in Hypertensive Patients: A Comparative Cross-sectional Study - Amr Setouhi; Mohammad-Alaa S. Taha; Alaa M. Ibrahim; Hazem M. A. Farrag (Journal of the Indian Academy of Echocardiography & Cardiovascular Imaging)
Background: Short-term blood pressure variability (BPV) has been associated with adverse cardiovascular outcomes, but its impact on left atrium (LA) function and structure remains unclear. This study aims to explore the relationship between short-term BPV and LA function in patients with controlled and uncontrolled hypertension, using speckle-tracking echocardiography (STE). Methods: In this cross-sectional study, 150 hypertensive patients were recruited and categorized into controlled and uncontrolled hypertension groups based on ambulatory blood pressure (BP) monitoring. BPV was calculated from 24-h ambulatory BP recordings, and LA function was assessed using STE to measure LA volume, strain, and strain rate parameters. Univariate and multivariate analyses were performed to investigate associations between BPV and LA functions. Results: Higher short-term BPV was significantly associated with impaired LA function, including reduced LA strain and increased LA volume index, in both hypertensive groups. After adjusting for confounding factors such as age, body mass index, and duration of hypertension, BPV remained an independent predictor of LA dysfunction (P < 0.01). The relationship was more pronounced in the uncontrolled hypertension group. Conclusion: Short-term BPV is independently associated with left atrial dysfunction in hypertensive patients, particularly in those with uncontrolled hypertension. These findings suggest that BPV could serve as a potential marker for early left atrial remodeling in hypertensive populations, providing insights for better risk stratification and management.